PENGARUH IKLIM ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Candrayanto Candrayanto; Rahmi Widyanti; Kurniaty Kurniaty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The background of this study by organizational climate and job discipline on employees performance of Politeknik Muara Teweh North Barito regency. This is affected by organizational climate, job discipline and employees performance. The purpose this study is how much influence the organizational climate, job discipline on employees performance of Politeknik Muara Teweh North Barito regency.The design of this study using quantitative methods. Data were collected through questionnaires to 54 respondents in the Politeknik Muara Teweh of North Barito regency by using sampling techniques proportionate stratified random sampling to determine the respondents to each variable. Then analysis of the data obtained in the form of quantitative analysis Quantitative Analysis of covering validity and reliability, hypothesis testing through F test and t test and analysis test, the coefficient of determination (R2). The data analysis technique used is the analysis of multiple linear regersi which serves to prove the hypothesis of the study.Results of the analysis found that the organizational climate variable (X1) of 40.2%, job discipline (X2) amounted to 63.8%, singly or together have a positive and significant impact on Employees performance (Y). Figures adjusted R-square of 0.892 indicates that 89.2% Employee performance variables influenced by three independent variables used in the regression equation. While the remaining 10.8% is explained by other variables outside the three variables used in this study. And it is known that the dominant variable affecting Employee performance variables are variables besides Organizational climate and Job discipline.